Platelet function alterations in dengue are associated with plasma leakage - Michels, Meta; Alisjahbana, Bachti; de Groot, Philip G.; Indrati, Agnes R.; Fijnheer, Rob; Puspita, Mita; Dewi, Intan M. W.; van de Wijer, Lisa; de Boer, Ellen M. S.; Roest, Mark; van der Ven, André J. A. M.; de Mast, Quirijn (Thrombosis and Haemostasis, 2014)
Severe dengue is characterised by thrombocytopenia, plasma leakage and bleeding. Platelets are important for preservation of endothelial integrity. We hypothesised that platelet activation with secondary platelet dysfunction contribute to plasma leakage. In adult Indonesian patients with acute dengue, we measured platelet activation status and the response to the platelet agonist TRAP using flow cytometerbased assays. Patients were monitored daily for plasma leakage by ultrasonography. Acute dengue was associated with platelet activation with an increased expression of the activated fibrinogen receptor (αIIbβ3), the lysosomal marker CD63 and the alpha-granule marker CD62P (P-selectin). Upon maximal platelet activation by TRAP, platelet function defects were observed with a significantly reduced maximal activated αIIbβ3 and CD63 expression and reduced platelet-monocyte and platelet-neutrophil complexes. Patients in the lowest tertile of activated αIIbβ3 and CD63 expression had an odds ratio for plasma leakage of 5.2 (95% confidence interval [CI] 1.3–22.7) and 3.9 (95% CI 1.1–13.7), respectively, compared to the highest tertile. Platelet-derived serotonin has previously been related to plasma leakage and we found increased intra-platelet serotonin concentrations in our patients. In conclusion, platelet activation with platelet function alterations can be found in patients with acute dengue and this may contribute to dengue-associated plasma leakage.
Keywords: Dengue virus infection; platelet function; flow cytometry; plasma leakage; serotonin